2018
DOI: 10.1016/j.ijnurstu.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the quality of the dying and death experience in the Emergency Department: An integrative literature review

Abstract: Sixteen articles are included. Eight themes emerged from the literature: care in the Emergency Department is about living not dying, staff perceive that death is a failure, staff feel underprepared to care for the dying patient and family in this environment, there is limited time for safe standards of care, staff stress and distress, staff use of distancing behaviours, the care of the dying role is devolved from medics to nurses at the end of life, and patients and staff perceive that the Emergency Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“… 5 The reality of a busy ED although is largely focussed on ‘saving’ lives, on curative approaches, and assessment for reversible illness and deterioration. 6 ED presentations for the patient who is at the end‐of‐life requires a change of focus to incorporate end‐of‐life care; 7 , 8 for example, recognising that a patient is dying, incorporation of shared decision‐making and possibly withdrawal of interventions. There is a perception that the ED is not a place for care of the dying; 8 however, dying occurs regularly in these settings and according to Wang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The reality of a busy ED although is largely focussed on ‘saving’ lives, on curative approaches, and assessment for reversible illness and deterioration. 6 ED presentations for the patient who is at the end‐of‐life requires a change of focus to incorporate end‐of‐life care; 7 , 8 for example, recognising that a patient is dying, incorporation of shared decision‐making and possibly withdrawal of interventions. There is a perception that the ED is not a place for care of the dying; 8 however, dying occurs regularly in these settings and according to Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“… 6 ED presentations for the patient who is at the end‐of‐life requires a change of focus to incorporate end‐of‐life care; 7 , 8 for example, recognising that a patient is dying, incorporation of shared decision‐making and possibly withdrawal of interventions. There is a perception that the ED is not a place for care of the dying; 8 however, dying occurs regularly in these settings and according to Wang et al . ‘EDs are an opportune entry point into the palliative care continuum’.…”
Section: Introductionmentioning
confidence: 99%
“…Providing compassionate and dignified end-of-life care in the emergency department is a longstanding and patient-centered practice where the emergency care sector has demonstrated a clear need for specialty-wide improvement. [10][11][12] Like many welldesigned disaster preparedness programs, the actual disaster did not create the full need for the planned program as the authors had anticipated, but the program development process, template, and educational tools are included here in JEN as a resource for program replication and testing in other emergency departments, regardless of pandemic conditions. 9 This issue of JEN also includes infectious disease-related manuscripts on topics of Ebola, 13 HIV, 14 rabies, 15 and PPE, 8,13 vaccine, 16 antibiotic, 17 antipyretic, 18 and phlebotomy 19 interventions.…”
Section: Infectious Disease Manuscripts In This Issue Of Jenmentioning
confidence: 99%
“…It is believed that patients with chronic end‐stage illnesses do not need life‐sustaining procedures or resuscitation but would benefit more from PC (Ke et al, 2020). However, the quality of death in the ED is grim (McCallum et al, 2018). Studies reported that dying patients were often exposed to a cold world and lost their dignity towards the end‐of‐life in the ED (Diaz‐Cortes et al, 2018; Fernandez‐Sola et al, 2018; Fernández‐Sola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a less than average level of PC competence among oncology nurses or nursing students across various healthcare settings globally (Laporte et al, 2020; Sawatzky et al, 2021; Shen et al, 2019). Insufficient perceived self‐competence in PC results in poor communication between healthcare teams (Moir et al, 2015), a heavy emotional burden on healthcare professionals (Bailey et al, 2011), lack of quality of life for dying patients (McCallum et al, 2018) and even absence of dignity towards the end of life (Granero‐Molina et al, 2016). Thus, perceived self‐competence in PC is a contributor to improved quality of life for patients and their families.…”
Section: Introductionmentioning
confidence: 99%